2017
DOI: 10.5812/numonthly.47051
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Pure Ultrasonography Guided Percutaneous Nephrolithotomy in Flank Position

Abstract: Background: Although percutaneous nephrolithotomy is most commonly performed with fluoroscopic access, yet, phobia and risks of radiation exposure are 2 important dilemmas. Herein the feasibility of flank position ultrasound guided percutaneous nephrolithotomy for management of renal stones was assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…In our study, the mean age of patients was 47.3 ± 7.6 (21-91) ( Table 1). A couple of other studies have given the same results; for instance, Zimmermanns et al reported on 652 patients with the mean age of 54.1 ± 15.7, and Zare studied 250 patients with the mean age of 42.0 ± 13.4 [8], [9]. The mean size of stone in our study was 19.4 ± 1.2 (12-60) mm ( Table 1).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In our study, the mean age of patients was 47.3 ± 7.6 (21-91) ( Table 1). A couple of other studies have given the same results; for instance, Zimmermanns et al reported on 652 patients with the mean age of 54.1 ± 15.7, and Zare studied 250 patients with the mean age of 42.0 ± 13.4 [8], [9]. The mean size of stone in our study was 19.4 ± 1.2 (12-60) mm ( Table 1).…”
Section: Discussionsupporting
confidence: 85%
“…According to Abdelhafez et al study in 2012, on 83 patients, simple stones accounted for 38.6%; multiple, complex stones accounted for 61.4% [3]. Zare recorded 62% of complex stones, 12% of pelvic renal stones, and 4% of upper ureteral stones [9]. Hydronephrosis degrees 1, 2, and 3 for the patients in our study group were 30.7%, 45.5%, and 13.3%, respectively (Table 1).…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations